Report on the 11th Conference of the Groupe des Cartothécaires de LIBER 15-18 September 1998, Kraków, Poland - Fleet, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
Based on the former LIBER Special Newsletters, this report attempts to provide a general summary of the conference, extracting salient details from each of the papers, and describing events in the order that they were presented at the conference. This is necessarily a subjective distillation of facts, in order to highlight general trends and provide briefer overviews, and readers are therefore referred to the complete versions of these papers, which will be published in The LIBER Quarterly, and also on the GdC Website ().